(untitled) (Ozone Therapy Global Journal, 2018)
Multidrug resistant bacterial isolates have significantly increased in recent years as a cause of bacterial cystitis. This increasing resistance to antimicrobial drugs leaves fewer therapeutic options for effective treatment. The emergence of antibiotic resistant bacteria in the community is necessitating the need to explore non-pharmocologic treatment options to reduce the spread and proliferation of these species. Ozone is an emerging therapy with both potent antibacterial properties and the ability to modulate the immune system, reduce oxidative stress induced by chronic infection and upregulate the endogenous antioxidant system providing further protection from free radical injury. In this case report, it is discuss how a patient with chronic ESBL-EC cystitis with limited therapeutic options was effectively treated with ozone therapy. It is shown a case study of a 67-year-old female with a neurogenic bladder who developed chronic cystitis caused by ESBL-producing and multi-drug resistant E. coli (ESBL-EC). It was treated with bladder instillations of ozonated distilled water, combined with Major Autohemotherapy (MAHT) as an adjunctive immune modulated support. The current findings show that the elimination of a case of chronic cystitis cause by ESBL-EC was effectively treated with an alternative to pharmacologic antimicrobial therapy utilizing distilled instillation of ozonated water and Major Autohemotherapy. Further studies are warranted to investigate this as a potential therapeutic option for this and other resistant bacterial infections.